2018
DOI: 10.1172/jci.insight.124152
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and immunoprofiles associated with fetal abnormalities of ZIKV-positive pregnancies

Abstract: Janeiro, along with 14 healthy pregnant controls in non-endemic Los Angeles. RESULTS. Extensive multiplexing analysis of 69 cytokines revealed that CXCL10, CCL2, and CCL8 chemokines were specifically associated with symptomatic ZIKV + infection during pregnancy, and distinct immunoprofiles were detected at different trimesters in ZIKV-infected pregnant women. Intriguingly, the high CCL2 level and its inverse correlation with CD163, TNFRSF1A, and CCL22 levels was apparently associated with ZIKV-induced abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 26 publications
(27 reference statements)
5
32
1
Order By: Relevance
“…Maternal blood levels of these cytokines were lower in the ZIKV group (although the difference was not statistically significant) ( S2 Fig ) that could potentially contribute to the lower cytokine levels in offspring. Previously described markers of maternal immune activation which may affect fetal health, IL-6 [43] and IL-17A [44] in the ZIKV group were lower or equal to that in control litters ( P ≥ 0.47); these data are in agreement with findings in pregnant women with acute ZIKV infection [45] and mice [12]. Also, IL-6 and IL-17A levels in ZIKV group did not change significantly throughout the experiment ( S2 Fig ); the same was found for maternal IL-1 β , IL-8, IL-10, IL-12, IL-13, IFN- β , and IFN-γ ( S2 Fig ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Maternal blood levels of these cytokines were lower in the ZIKV group (although the difference was not statistically significant) ( S2 Fig ) that could potentially contribute to the lower cytokine levels in offspring. Previously described markers of maternal immune activation which may affect fetal health, IL-6 [43] and IL-17A [44] in the ZIKV group were lower or equal to that in control litters ( P ≥ 0.47); these data are in agreement with findings in pregnant women with acute ZIKV infection [45] and mice [12]. Also, IL-6 and IL-17A levels in ZIKV group did not change significantly throughout the experiment ( S2 Fig ); the same was found for maternal IL-1 β , IL-8, IL-10, IL-12, IL-13, IFN- β , and IFN-γ ( S2 Fig ).…”
Section: Resultssupporting
confidence: 89%
“…To our knowledge, type I IFN profiles in human fetuses and offspring affected with ZIKV infection were not addressed, yet. However, it has been shown that acute ZIKV infection is associated with increased IFN-α levels in the blood sera of pregnant women [45]. Human infections with other related flaviviruses (dengue virus and West Nile virus) were also associated with increased IFN-α levels in the blood plasma/sera [86,87].…”
Section: Discussionmentioning
confidence: 99%
“…Corroborating these results, it has been shown that CCL2 levels were found to be increased in the amniotic fluid of ZIKV-positive women giving birth to babies with neonatal microcephaly, relative to uninfected control group [50]. Similarly, CXCL10, a chemokine that has been associated with neuronal damage, was the most highly induced inflammatory factor in symptomatic ZIKV-positive pregnant women and was also specifically elevated in pregnant women with abnormal birth outcomes [49,51]. Therefore, the elevated levels of these chemokines could be playing a detrimental role in ZIKV-infected embryo brains.…”
Section: Discussionmentioning
confidence: 95%
“…Increased transcriptional levels of the chemokines CCL2, CXCL1 and CXCL10 in the brain of ZIKV-positive embryos could indicate the increased recruitment of inflammatory cells, facilitating viral elimination, but also exacerbating neuroinflammation. Interestingly, it has been shown that CCL2 levels are increased in ZIKV-infected pregnant women [49]. Notably, CCL2 was found to be the most highly induced inflammatory factor in ZIKV-positive pregnant women with abnormal birth outcomes, as compared to that of ZIKV-positive pregnant women without birth complications [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation